PELATIHAN DAN PENDAMPINGAN PERBANYAKAN TANAMAN PAKAN KUPU-KUPU BAGI MASYARAKAT NIMBOKRANG KABUPATEN JAYAPURA - Ignatius Joko Suyono; Linus Yhani Chrystomo; I Made Budi (LPPM Uncen, 2019)
Community service have the title Training and Accompaniment Propagation of Butterfly Feed Plants for the Nimbokrang Community Jayapura Regency was carried out to provide benefits to the Nimbokrang community of Jayapura Regency who wished to develop their area into a natural tourist destination. The purpose of this service is to provide education, training and assistance in the multiplication of butterfly feed plant seedlings so that the Rhepang Village Nimbokrang community has the skills to make butterfly feed plant seedlings. The benefits of breeding skills of butterfly feed plants can be used to develop the area that wants the area to make a natural tourist destination. Planting a butterfly feed plant, which is mostly a kind of colorful flower plants, can attract the arrival of butterflies in the area so that it can add to the beauty of attractiveness and add to the vibrant natural tourism area. The dedication method used was education, training and mentoring that provided the skills for making butterfly feed plant seedings for the people of Rhepang Village Nimbokrang and assistance to provide concrete examples of how to make butterfly feed plant seedinds in the field. As a result of this dedication activity, the people of Rhepang Village Nimbokrang gained knowledge and skills in how to multiply butterfly feed plants. The scientific output of the community service was published in one of the service journals, the namely is the Papua Service Journal.Keywords: Nursery, butterfly feed plants, community skills and knoledge, Rhepang Village Nimbokrang, the beauty of natural tourism